Conversational Maxims and Persuasive Communication: Verbal Offer Strategies Among Sellers in Aceh Traditional Markets - Cut Nurul Azmar; Kismullah Abdul Muthalib; Yunisrina Qismullah Yusuf; Septhia Irnanda; Asma Sohaib Khan (Center of Language Development, Institut Agama Islam Negeri Madura, 2025)
This research explores the use of conversational maxims and verbal offers in traditional market interactions in Pasar Aceh, Banda Aceh, Indonesia, aiming to expand the understanding of communication strategies that enhance seller-customer interactions. Despite extensive studies on Grice's Cooperative Principle in various contexts, limited research has examined how sellers in traditional markets strategically engage with these maxims to persuade customers. The study involved detailed observations, audio recordings, and interviews with eight Acehnese clothing sellers chosen for their active roles in daily market interactions. Using Grice's Cooperative Principle, which includes the maxims of quantity, quality, relevance, and manner, the findings reveal that these eight sellers strategically employ these maxims to persuade customers, with occasional variations encouraging smoother and more effective interactions. The analysis identified seven distinct verbal offer types: direct product mentions, polite customer calls, pricing discussions, product origin mentions, customer needs assessment, store entry invitations, and color-based product promotions. These findings provide a grounded theory of seller-customer interactions in traditional markets, presenting persuasive techniques that may enhance market engagement and consumer satisfaction. This study provides communication patterns within traditional market settings, especially in Aceh, and cross-cultural market communication research.